Study on proteinase inhibitors and antibacterial activity of coirama (Kalanchoe pinata) leaf juice - Thuy, Dao Thi; Ha, Hoang Thu; Tran Chau, Pham Thi (Academia Journal of Biology, 2014)
As known, proteinases are involved in different living processes including infectious, inflammation process. Therefore study proteinase inhibitors in medicinal plants possess effect of treatment the mention above diseases might contribute to understanding their action mechanism. Juice of fresh Kalanchoe leaves has been used effectively for treatment of various diseases including inflammation, skin ulcers, wound, burn. There were many publications about chemicals isolated from these leaves and their biological activities, but none of them concerning proteinase inhibitors. This work deals with proteinase inhibitors (PIs) from Kalanchoe leaf juice and searching for their antibacterial activity and effect on proteinases isolated from P. aeruginosa and S. aureus. Three Kalanchoe leaves differed from each other in their figures, designated as K1, K2, K3 were chosen for our study. The obtained results documented that: Kalanchoe leaf juice inhibited growth of all tested S. aureus samples isolated from pus of patients. However, the antibacterial activity of leaf - peduncle juice was lower than that of leaf-blade juice. Leaf juice of K1, K3 exhibited inhibitory activity against trypsin, chymotrypsin and proteinases isolated from P. aeruginosa and S. aureus. By fractionating the liophylized K1 leaf juice preparation on Sephadex G-25 column and measuring absorption at 280 nm of eluted fractions, two peaks on chromatogram were observed. The main peak 1 (D1) reduced proteolytic activity of trypsin, chymotrypsin and proteinases from P. aeruginosa. Peak 1 also inhibited growth of P. aeruginosa. Counting inhibitory specific activity (mIU/mg protein) of the liophylized juice preparations shoved that the specific activity against proteinases from P. aeruginosa was higher than that against trypsin and chymotrypsin about 2 to 8 time. Thus, it was suggested that PI in leaf juice may play an important role in the antibacterial activity of K1 leaf juice.